Early Christianity in the Lycus Valley - Huttner, U. (Ulrich) (Ancient Judaism and early Christianity, 2013)
With Early Christianity in the Lycus Valley Ulrich Huttner offers a microstudy of Christian history in southwestern Asia Minor (first to fifth century C.E.).